2019
DOI: 10.2147/ceg.s228203
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Helicobacter pylori</em> And Duodenal Ulcer: Systematic Review Of Controversies In Causation</p>

Abstract: BackgroundThere are controversies on the causal role of H. pylori in duodenal ulceration. Helicobacter pylori are curved gram-negative microaerophilic bacteria found at the layer of gastric mucous or adherent to the epithelial lining of the stomach. It’s a public health significance bacteria starting from discovery, and the prevalence and severity of the infection varies considerably among populations. H. pylori are a risk for various diseases, while the extent of host response like gastric inflammation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Peptic ulcer disease is more prevalent in Asian than Western populations, 6–8 and the fatality rate remains high at approximately 3–10% 1,5 . Helicobacter pylori infection is a major risk factor for gastric or duodenal ulcers, contributing to an estimated 85% of cases 1,6,9 . An epidemiologic study found that 93% of Chinese patients with peptic ulcer disease had H. pylori infection 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptic ulcer disease is more prevalent in Asian than Western populations, 6–8 and the fatality rate remains high at approximately 3–10% 1,5 . Helicobacter pylori infection is a major risk factor for gastric or duodenal ulcers, contributing to an estimated 85% of cases 1,6,9 . An epidemiologic study found that 93% of Chinese patients with peptic ulcer disease had H. pylori infection 6 .…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Helicobacter pylori infection is a major risk factor for gastric or duodenal ulcers, contributing to an estimated 85% of cases. 1,6,9 An epidemiologic study found that 93% of Chinese patients with peptic ulcer disease had H. pylori infection. 6 H. pylori infection is associated with a sixfold increased risk of developing gastric cancer, 10 and H. pylori antibiotic resistance is increasing, 11 especially in Asia where clarithromycin and metronidazole resistance rates are high (> 15%).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of this disease is about 1 in 600 emergency presentations during usual months, but various studies published in Pakistan have observed that the incidence of PDU becomes higher during the holy month of Ramadan. Apart from the various general factors such as use of non-steroidal anti-inflammatory drugs, smoking, stress-related disorders, and Helicobacter pylori infection contributing most of the cases [9][10][11][12], certain other factors such as prolonged fasting contribute to its higher incidence in Ramadan [13]. Laparoscopy was introduced in the ED of Holy Family Hospital, Rawalpindi, Pakistan, three years back.…”
Section: Introductionmentioning
confidence: 99%
“…However, greater acceptance of laparoscopy in recent years has encouraged surgeons to use it due to its proven benefits of less pain, short hospital stays, faster recuperation, and decreased morbidity [ 4 - 6 ]. Performing diagnostic laparoscopy in cases of suspected viscous perforation or peritonitis has the advantage of identifying an occasionally unexpected pathology.…”
Section: Introductionmentioning
confidence: 99%